Children with medical complexity: the change in the pediatric epidemiology - Rino Agostiniani; Laura Nanni; Tommaso Langiano (Hygeia Press di Corridori Marinella, 2014)
In the last years, epidemiological landscape of pediatric illness is changed; we are facing a progressive raising of the number of children affected by chronic illness (children with special health care needs [CSHCN]), mainly due to the amelioration in surviving and in care. These patients have become the majority of the inpatients in some specialist hospitals, like the Meyer Children's Hospital (Florence, Italy), in 2012. One important group of CSHCN is represented by the children who are most medically fragile and have the most intensive health care needs (children with medical complexity [CMC]). In these patients, the complexity of the pathological framework frequently results in a plenty of visits and tests, with high risk of redundant and expensive cares. They also need outside support networks such as advocacy and accommodations at school, at home, in social life. The CMC needs specific skill and new strategies that could involve pediatricians in hospital as in home care. The professional competencies are ready but a clear and shared strategy is lacking.   Proceedings of the 10th International Workshop on Neonatology · Cagliari (Italy) · October 22nd-25th, 2014 · The last ten years, the next ten years in Neonatology Guest Editors: Vassilios Fanos, Michele Mussap, Gavino Faa, Apostolos Papageorgiou